2020
DOI: 10.1002/alr.22509
|View full text |Cite
|
Sign up to set email alerts
|

Treatment‐related morbidity in patients treated for sinonasal malignancy

Abstract: Background: Sinonasal malignancies are a rare, heterogeneous group of tumors that o en present at an advanced stage and require multimodal therapy. The presence of high-grade toxicity and sinonasal complications a er treatment can negatively impact quality of life. In this study we aim to describe pos reatment morbidity in patients with sinonasal malignancy. Methods:A retrospective analysis of all patients treated for sinonasal malignancy was conducted from 2005 to 2018 at a tertiary referral institution. A to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…A prospective national study has been initiated with the aim of investigating cerebral toxicity after radiotherapy for SNM following Sharma et al , (2020)'s study which showed significant late neurotoxicity with macroscopic and cognitive impairment present on both hippocampi, both frontal lobes and the right temporal lobe [60 ▪▪ ]. High grade radiation toxicity was also found in Patel et al (2020)'s study with a subset of patients requiring endoscopic sinus surgery post radiation due to chronic sinusitis and another group needing operative debridement due to symptomatic nasal obstruction [61].…”
Section: Introductionmentioning
confidence: 97%
“…A prospective national study has been initiated with the aim of investigating cerebral toxicity after radiotherapy for SNM following Sharma et al , (2020)'s study which showed significant late neurotoxicity with macroscopic and cognitive impairment present on both hippocampi, both frontal lobes and the right temporal lobe [60 ▪▪ ]. High grade radiation toxicity was also found in Patel et al (2020)'s study with a subset of patients requiring endoscopic sinus surgery post radiation due to chronic sinusitis and another group needing operative debridement due to symptomatic nasal obstruction [61].…”
Section: Introductionmentioning
confidence: 97%
“…SNC patients experience acute worsening of sinonasal symptoms was measured using the SNOT‐22 questionnaire in the first few months of treatment followed by recovery after approximately 2 years; however, this does not return to baseline 44 . At least 20% of irradiated patients had post‐radiation sinusitis requiring a functional endoscopic sinus surgery (ESS) 87 . While post‐radiation ESS is safe and alleviates sinonasal symptoms, it may not reduce nasal crusting.…”
Section: Resultsmentioning
confidence: 99%
“…44 At least 20% of irradiated patients had post-radiation sinusitis requiring a functional endoscopic sinus surgery (ESS). 87 While post-radiation ESS is safe and alleviates sinonasal symptoms, it may not reduce nasal crusting. Insufficient evidence exists to confirm whether pre-radiation functional ESS is beneficial to patients, although some surgeons advocate for opening the sinuses during advanced sinonasal or skullbase surgery.…”
Section: Late Effects: Sinonasal and Olfactionmentioning
confidence: 99%
“…1). This exposure to low to moderate levels of radiation can potentially lead to both acute and chronic adverse effects [17,18]. These chronic toxicities, such as ocular and neurologic injuries,…”
Section: Intensity-modulated Radiation Therapy and Intensity-modulate...mentioning
confidence: 99%